Basic Fundamental Family Care Given to Prevent Morbidity in Renal Transplant Recipients of India. (August 2017) - Patil, Mayur; Kute, Vivek; Patel, Himanshu; Shah, Pankaj; Trivedi, Hargowind
Abstract : Kidney transplants are on a constant rise in developing country like India. More and more chronic kidney disease patients are going in for renal transplantation 1, 2 . In India, the level of health care is still moderate and with an ever expanding population the rate of spread of infections is very high. The most susceptible person to these infections is an organ transplant recipient. Moreover, in India, the average organ transplant recipient is less educated to take care of himself, with a tendency to have carelessness in terms of taking medicines and maintenance of hygiene. This is where the family care and pressure becomes utmost important to maintain smooth functioning of graft. In this study, we gave a questionnaire and discussed personally with the care givers regarding the level of care at home and the steps being taken to prevent morbidity. We found that boiling drinking water was the common modality performed by 98% of families as reverse osmosis drinking water facility is not readily available to an average Indian family. Diet chart was strictly followed by 78% care givers. Different restrictions to prevent infections like compulsory wearing a face mask, avoiding crowded places and cutting the number of visitors at home, were strictly implemented by family members. In pediatric recipients, 35% children were prevented from going to school for 3 months to prevent infections. With respect to immunosuppressant medicines, proper dispenser boxes were prepared to avoid skipping dosage. Periodic hematological checkup at nearest laboratory was regularly performed. Home blood sugar testing with glucometer was learnt and followed by family members of diabetic patients. A regular follow up as per the given schedule was ensured by care givers. Strict avoidance of smoking and alcohol was implemented. Light exercise and yoga has been made a part of daily routine. Most common primary care giver found in our study was mother (72%) followed by wife (16%). In 58%, mother was both donor as well as primary care giver. Family care was given to the recipient as well as donor. A major aspect of transplant is psychological support, was provided by family members and not psychiatrist3. We concluded that in an emerging economy like India, such small yet important steps taken can avoid morbidity in recipient. The primary treating physician cannot take care of every aspect and thus it is this family who ensures the smooth functioning of graft along with the physician. References: 1. Shroff S. Current trends in kidney transplantation in India. Indian Journal of Urology: IJU: Journal of the Urological Society of India . 2016;32(3):173-174. doi:10.4103/0970-1591.185092. 2. Shroff S. Indian transplant registry. Indian Journal of Urology: IJU: Journal of the Urological Society of India . 2007;23(3):272-277. doi:10.4103/0970-1591.33724. 3. Naqvi R. Evaluation of psychiatric issues in renal transplant setting. Indian Journal of Nephrology. 2015;25(6):321-325. doi:10.4103/0971-4065.165006.